RANCANGAN MODEL PURWARUPA KEMASAN KOPI SPECIALTY - Zulkarnain; Machfud; Marimin; Emmy Darmawati; Sugiarto (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Packaging design is a challenge for the development of micro-industries, especially to encounter high competition against well-known products. Unfortunately, most of micro-industries have limitations in term of packaging design and attractiveness. The purpose of this study was to design the right packaging prototype model for the micro-industries. The study applied the value engineering approach which consisted of information, creative, analysis, development, and recommendation stages. In the creative stage, the process included making the moodboards, sketches and digitizing designs as well as generating prototypes. Fuzzy AHP (Analytical Hierarchy Process) was applied in the analysis stage to obtain the weight of each performance parameter. From the analysis, it found that colour was the most significant parameter in determining packaging design of specialty coffee packaging. The most appropriate model recommendation as a representation of packaging for specialty coffee businesses for micro-scale industries was the flat bottom pouch type contained in alternative III. Keywords: fuzzy AHP, packaging design, prototype, value engineering